2002
DOI: 10.1139/b02-013
|View full text |Cite
|
Sign up to set email alerts
|

Demographic structure of three species ofSarcocapnos(Fumariaceae) as a basis for their conservation

Abstract: The genus Sarcocapnos DC., endemic to the western Mediterranean basin, contains seven species, all of which are rare. Monthly monitoring of the number and flowering status of individuals as well as the appearance of new seedlings in five populations of three species, Sarcocapnos baetica (Boiss. & Reuter) Nyman, Sarcocapnos enneaphylla (L.) DC., and Sarcocapnos pulcherrima Morales & Romero-García, was conducted between July 1997 and June 1998. This monitoring was repeated in May 1999 and 2000. Given the difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Habit: 0 = perennial, 1 = annual, 2 = biennial All members of Sarcocapnos are perennial except for S. enneaphylla which is described as both annual and perennial (Salinas et al 2002). 2.…”
Section: Resultsmentioning
confidence: 99%
“…Habit: 0 = perennial, 1 = annual, 2 = biennial All members of Sarcocapnos are perennial except for S. enneaphylla which is described as both annual and perennial (Salinas et al 2002). 2.…”
Section: Resultsmentioning
confidence: 99%
“…A demographic comparison of three species of Pinguicula (Lentibulariaceae) revealed that the most geographically widespread species (P. villosa) had the shortest lifespan and greatest between-year variation in density (Svensson et al (Fumariaceae), the most widespread species (S. enneaphylla) had the shortest life span (Salinas et al 2002). More widely, Rabinowitz et al 1989) also found that rare prairie species were less variable in abundance from year to year than more common species.…”
Section: Comparisons Among the Myosotis Speciesmentioning
confidence: 99%